2016
DOI: 10.1007/s00467-016-3461-y
|View full text |Cite
|
Sign up to set email alerts
|

Is there such a thing as biocompatible peritoneal dialysis fluid?

Abstract: Introduction of the so-called biocompatible peritoneal dialysis (PD) fluids was based on a large body of experimental evidence and various clinical trials suggesting important clinical benefits. Of these, until now, only preservation of residual renal function—likely due to lower glucose degradation product load and, in case of icodextrin, improved fluid and blood pressure control—have consistently been proven, whereas the impact on important clinical endpoints such as infectious complications, preservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…The inflammation and endothelial injury caused by peritonitis or other factors are believed to cause high vascular permeability and fibrin exudation based on PD related vasculopathy in progressive EPS cases. Repetitive peritonitis also causes angiogenesis, with vessels expanding beyond the three distinct vascular layers found in normal peritoneum [17,57]. IL-6 is thought to be a mediator of increased solute transport related to infection, seen in an IL-6 KO peritonitis model [58], and supported by clinical findings of elevated level of IL-6 in PD effluent [59].…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 55%
See 1 more Smart Citation
“…The inflammation and endothelial injury caused by peritonitis or other factors are believed to cause high vascular permeability and fibrin exudation based on PD related vasculopathy in progressive EPS cases. Repetitive peritonitis also causes angiogenesis, with vessels expanding beyond the three distinct vascular layers found in normal peritoneum [17,57]. IL-6 is thought to be a mediator of increased solute transport related to infection, seen in an IL-6 KO peritonitis model [58], and supported by clinical findings of elevated level of IL-6 in PD effluent [59].…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 55%
“…However, the impact on peritoneal membrane transport function has not been quantified by meta-analysis [96][97][98]. Last but not least, biocompatible PD solution is not fully biocompatible, and still needs to be improved to counter unsolved problems such as infection, PD membrane preservation, and patient survival (for review [57]). One prospective observational study, "Neutral solution, Extraneal use, and current PD outcome in Japan (NEXT-PD)" [99] showed that multidisciplinary approaches including the use of biocompatible PD solution, reduction of high glucose solutions, introduction of an incremental prescription style [100], combination therapy (PD and hemodialysis) [101], and planned PD discontinuation for long-term cases with membrane damage [101] contributed to a decreased incidence of EPS [99,102].…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 99%
“…The progressive nature of CKD and the subsequent end stage renal disease (ESRD) are putting a substantial burden on global health-care resources. It had been estimated that 2.3 million patients globally would have ESRD by the end of 2008, and that number already increased to doi: https://doi.org/10.15407/ubj90.02.034 3.37 million by the end of 2014. This rise represents a 46.5% increase in 6 years [1,2].…”
mentioning
confidence: 99%
“…PD has been reported as one of the convenient, safe and efficient modalities of RRT during the last 50 years. Treatment with PD allows RRT to be performed at home and thus maintains a better integration of the patient into normal social life, even though it imposes a major burden on families [2,3]. Other advantages of PD are lower hemodynamic stress, longer preservation of residual renal function, and potential cost savings [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation